Effectiveness of a Dutch community-based alcohol intervention: Changes in alcohol use of adolescents after 1 and 5 years. (1st February 2016) - Jansen, Sophia C.; Haveman-Nies, Annemien; Bos-Oude Groeniger, Inge; Izeboud, Cobi; de Rover, Carolien; van't Veer, Pieter
Highlights: This community intervention appears to be effective in reducing alcohol use. The effect was restricted to adolescents in the second grade of high school. The effect remained after 5 years of intervention. Abstract: Background: Underage alcohol drinking is a severe public health problem. The aim of this study was to evaluate the short- and long-term effects of a Dutch community-based alcohol intervention on alcohol use of adolescents in the second and fourth grade of high school. Methods: The community intervention integrated health education, regulation, and enforcement in multiple settings, targeting adolescents as well as their environments. In order to evaluate effectiveness, a quasi-experimental pretest posttest design was used based on three independent cross-sectional surveys in 2003, 2007 and 2011, resulting in an analytical sample of approximately 5700 and 3100 adolescents in the intervention and reference region, respectively. For the main analyses, we compared the change in recent alcohol use and binge drinking in the intervention region with the reference region. Linear regression was used to obtain (adjusted) prevalence of alcohol use. Results: During the study period, there was an overall decline in the prevalence of alcohol use. After 1 year of intervention, the decline was 11% ( P < 0.01) and 6% ( P < 0.01) stronger in the intervention region as compared to the reference region, for recent alcohol use and binge drinking respectively. This effect was restricted to the second grade and remained after 5 years of intervention. No clear subgroup effects or confounding were observed for ethnicity, gender or educational level. Conclusions: The Dutch community intervention appears to be effective on the short- and long-term in reducing the prevalence of recent alcohol use and binge drinking of (underage) adolescents in the second grade of high school.